Solvatochromism and side chain effects on the morphological behavior of bodipy-alt-i-Indigo copolymers - Singh, Anup Kumar; Swain, Gitanjali; Birajdar, Sarika (New Journal of Chemistry, 2024)
Among the factors that govern the self-assembly of a molecular system, side chains and solvent polarity play crucial roles in the morphological alteration of small molecules in solutions. Although the effect of side chains on the self-assembly of small molecules has been studied well, reports on their importance in the aggregation behavior of polymers are limited. Investigating whether a minor change in the side chain produce any significant impact on the morphology of the polymer in solution is of great research interest. Towards the end goal, to alter the morphology of polymers and to know the impact of the side chains on the self-assembly properties of the conjugated polymers, two BODIPY-i-Indigo alternating copolymers, P1 [poly(BDP12-alt-iI)] and P2 [poly(BDPE-alt-iI)], were synthesized, and their aggregation behavior was explored in various solvents. Both the copolymers, P1 and P2, exhibited narrow PDI values of 1.16 and 1.45, respectively. Although their cores are the same, P1 showed a thin film morphology, while P2 displayed a porous morphology (approximately 557 nm) in chloroform. On changing the solvent, P1 showed a porous morphology in a 50% THF-CHCl3 mixture. However, in P2, the pores were reduced to extremely small sizes in the 50% THF-CHCl3 mixture. This work demonstrates that even a minimal change in the side chains of copolymers and polarity differences between solvents can produce a drastic morphological effect.

Synergistic effect of lactam and pyridine nitrogen on polysulfide chemisorption and electrocatalysis in lithium sulfur batteries - Javaregowda, Bharathkumar H.; Kargude, Radhakisan; Birajdar, Sarika; Shivankar, Bhavana; Krishnamurty, Sailaja; Jones, Lathe A.; Caruso, Rachel A.; Krishnamoorthy, Kothandam (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: Li-S battery; phenyl-diketopyrrolopyrrole; pyridine-diketopyrrolopyrrole